Periodontal Status of Patients with Non -Insulin Dependent Diabetes Mellitus - Aryal, Sameer; Adhikari, Binod; Agrawal, Reshu; Bhuju, Krishna Gopal; Karki, Riwas (Journal of Nepalese Society of Periodontology and Oral Implantology, 2019)
Introduction: Association of Diabetes Mellitus and periodontal disease has been well established over the last few decades. It is a well established risk factor in the pathogenesis of periodontal disease. Objective: This study was conducted to assess the prevalence of periodontal disease in non-insulin dependent diabetes mellitus. Methods: Individuals with non-insulin dependent diabetes mellitus for the duration of at least five years were selected. Plaque Index (PII), Gingival Index (GI), Loss of attachment (LA) and Probing Depth (PD) were recorded using William’s Periodontal probe. Results: Patients with Non-Insulin Dependent Diabetes Mellitus demonstrated higher loss of attachment. Conclusion: The results showed statistically significant association between non-insulin dependent diabetes mellitus and periodontal disease thus supporting it as a risk factor for periodontitis.